Editorial - Gandin, Luís Armando; Icle, Gilberto; Farenzena, Nalú; Rickes, Simone Moschen (Educação & Realidade, 2011)
Editorial - Revista Educação & Realidade Volume 36 Número 3 - Língua, Discurso e Sujeito na Educação.